The Mathematics Education of Prospective Secondary Teachers Around the World - Strutchens, Marilyn E.; Huang, Rongjin; Losano, Leticia; Potari, Despina; Cyrino, Márcia Cristina de Costa Trindade; da Ponte, João Pedro; Zbiek, Rose Mary (ICME-13 Topical Surveys, 2017)
This volume shares and discusses significant new trends and developments in research and practices related to various aspects of preparing prospective secondary mathematics teachers from 2005-2015. It provides both an overview of the current state-of-the-art and outstanding recent research reports from an international perspective. The authors completed a thorough review of the literature by examining major journals in the field of mathematics education, and other journals related to teacher education and technology. The systematic review includes four major themes: field experiences; technologies, tools and resources; teachers' knowledge; and teachers' professional identities. Each of them is presented regarding theoretical perspectives, methodologies, and major findings. Then the authors discuss what is known in the field and what we still need to know related to the major topics.